2009
DOI: 10.2337/db08-0775
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Attenuates Insulin-Mediated Increases in Endothelial Cell Signaling but Augments Skeletal Muscle Insulin Action via Differential Effects on Tumor Necrosis Factor-α Expression

Abstract: OBJECTIVE The cytokine interleukin-6 (IL-6) stimulates AMP-activated protein kinase (AMPK) and insulin signaling in skeletal muscle, both of which result in the activation of endothelial nitric oxide synthase (eNOS). We hypothesized that IL-6 promotes endothelial cell signaling and capillary recruitment in vivo, contributing to increased glucose uptake. RESEARCH DESIGN AND METHODS The effect of IL-6 with and without insulin on AMPK, insulin, and eNOS signaling in and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 47 publications
2
36
0
3
Order By: Relevance
“…In addition, IL-6 has recently been reported to impair insulin signaling in vascular ECs (52). These findings suggest that these cytokines might inhibit insulin uptake not only through inhibition of caveolin-1 protein synthesis but also through inhibition of insulin signaling (20,49,52).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, IL-6 has recently been reported to impair insulin signaling in vascular ECs (52). These findings suggest that these cytokines might inhibit insulin uptake not only through inhibition of caveolin-1 protein synthesis but also through inhibition of insulin signaling (20,49,52).…”
Section: Discussionmentioning
confidence: 82%
“…In other studies TNF␣ and IL-6 (20 ng/ml each for 24 h) have been found to inhibit IRS-1 expression and insulin-stimulated IRS-1 tyrosine phosphorylation, although insulin-stimulated IR tyrosine phosphorylation appeared unaffected (37). In addition, IL-6 has recently been reported to impair insulin signaling in vascular ECs (52). These findings suggest that these cytokines might inhibit insulin uptake not only through inhibition of caveolin-1 protein synthesis but also through inhibition of insulin signaling (20,49,52).…”
Section: Discussionmentioning
confidence: 99%
“…The IL-6 serum concentrations increase up to 100-fold so that systemic effects are possible, e.g. the promotion of insulin resistance and lipolysis, whereas in skeletal muscle insulin action is augmented [70]. It seems difficult to reconcile this systemic pro-inflammatory effect of intense muscle work with the observed anti-inflammatory effect of regular exercise [46,71].…”
Section: Muscle Workmentioning
confidence: 99%
“…The proposition that carbohydrate availability is linked with cytokine expression is further strengthened by the observation that the provision of exogenous carbohydrate has a suppressive effect on plasma IL6 concentration (Nieman et al 1998, Febbraio et al 2003. The activity of AMPK has been proposed as an intracellular signal that governs skeletal muscle cytokine expression (Weigert et al 2007), but another study suggests that AMPK activity is increased by IL6 (Yuen et al 2009). Furthermore, Lihn et al (2008) reported that cytokine expression is reduced by AMPK activity.…”
Section: The Effect Of Exercise On Cytokine Expressionmentioning
confidence: 99%